Development of an electrocoagulation equipment for wall paint wastewater treatment (2020)
(Eng) This article describes the tests carried out to evaluate the process efficiency water treatment by electrocoagulation in construction paint wastewater. Electrocoagulation process consists of an electro lytic reactor, equipped with a current source and electrodes responsible for providing the destabilizing ions of colloidal particles, so that they replace the function of the chemical compounds used in conventional wastewater treatment. For the experimenta l design, we use drinking water and wall paint, in order to treat the solution by electrocoagulation in a treatment scale plant to compare the results before and after treatment, the variables to be measured are: dissolved oxygen (DO); turbidity; pH; condu ctivity; temperature; chemical oxygen demand (COD).After review the efficiencies obtained, we proceed to the development of an equipment treatment that can treat the wastewater from washing brushes and rollers to be reused again in the washing, avoiding co ntamination caused by washing tools after painting surfaces in construction processes